2009
DOI: 10.1007/s11104-009-0204-x
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of fertilizer practices on environmental risk of nitrate in semiarid farmlands in the Loess Plateau of China

Abstract: The lack of understanding of nitrate dynamics in soil profiles of semiarid regions hampers the assessment of the environmental risks associated with nitrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 35 publications
4
18
0
Order By: Relevance
“…This indicated that, except for that at 0 kg N ha −1 (maintained at 57 kg ha −1 ), NR was present in the soil and gradually accumulated, even at N rates as low as 80 kg N ha −1 . A similar phenomenon was also shown in the work of Guo et al (2010). In the North China Plain, nitrate-N successively accumulated in the top 100 cm of soil over two years, with average yearly increases as high as 48, 187, and 255 kg N ha −1 corresponding to N applications of 120, 240, and 360 kg N ha −1 in a winter wheat and maize system (Liu et al, 2003).…”
Section: Residual Nitrate-n In Soil At Harvestsupporting
confidence: 81%
“…This indicated that, except for that at 0 kg N ha −1 (maintained at 57 kg ha −1 ), NR was present in the soil and gradually accumulated, even at N rates as low as 80 kg N ha −1 . A similar phenomenon was also shown in the work of Guo et al (2010). In the North China Plain, nitrate-N successively accumulated in the top 100 cm of soil over two years, with average yearly increases as high as 48, 187, and 255 kg N ha −1 corresponding to N applications of 120, 240, and 360 kg N ha −1 in a winter wheat and maize system (Liu et al, 2003).…”
Section: Residual Nitrate-n In Soil At Harvestsupporting
confidence: 81%
“…We found that residual N, as Downloaded by [New York University] was expected, increased with added manure and sewage sludge, as it was dependent on the added available N, but this increase was not proportional compared to the level of added N (Figure 3). Other works have also found this nonproportional NO 3 -N rootzone accumulation in organic amendment treatments compared to conventional fertilizers (e.g., Guo et al 2010). In the first year SS-2 and SS-3 were significantly different from the control, whereas in the second year M-2 (along with the former two treatments) was also different from the control.…”
supporting
confidence: 51%
“…Guo et al . 22 found that N fertilizers coupled with farm yard manure resulted in 70% less NO 3 − -N accumulation in the soil profiles than that using mineral N fertilizer alone. However, some researches had found that manure applications without any pretreatment could cause serious NO 3 − -N leaching 23,24 .…”
Section: Introductionmentioning
confidence: 94%